Encountering deception in virtual spaces: guidelines for virtual ethnography - Owens, Lisa Lucile (Frontiers in Sociology, 2023)
This Perspective Essay draws from an experience of deception in virtual fieldwork and considers implications for those designing methodologies for virtual ethnographies. As qualitative field work increasingly takes place within virtual spaces and through virtual means, researchers are faced with critical dilemmas in the processes of data gathering and verification. One of these dilemmas concerns ensuring data validity and facticity if encountered with research subjects who are deceptive about their identity, experiences, or relationship to the field of research. This Perspective Essay offers specific guidelines concerning articulating the nature and possibilities of deception in virtual spaces, identifying deceptive data, and what to do with deceptive data in order to maintain data validity and transparency.